Implementasi Contextual Teaching And Learning (CTL) Dalam Meningkatkan Prestasi Belajar Siswa Pada Materi Bahasa Arab: (Studi Kasus di MTs Nurul Jadid Paiton Probolinggo) - Rifa'i, Moh; Hasanah, Iradatul; Zubairi, Zubairi; Sa’ad, Mukhlisin (STAI Asy-Syukriyyah, 2022)
Student achievement improvement in sub-subjects can be done with various methods so that it can be achieved. CTL (Contextual Teaching and Learning) is one of them. This research was conducted using a qualitative method, a case study type. Informants from KSK FAZA MTs Nurul Jadid through interviews, observation and documentation. Analysis of the data with data collection, data reduction and conclusion. The validity of the data using triangulation (researchers, data sources, methods and theories). The results of the study explained that the implementation of CTL in improving student learning achievement in Arabic material was carried out by applying story-based media in improving maharah kitabah, through two stages, namely in the odd semester mufrodat enrichment, text analysis, and composing simple sentences. In the even semester giving meaning with synonyms of the same sentence, memorizing, depositing, writing understanding and narrative descriptions. While the inhibiting factors in the ineffectiveness of effective days are caused by Pesantren or regional activities that require KSK students to attend, short duration of learning time, lack of mastery of mufrodat, varying students' ability to grasp subject matter. While the supporting factors for the application of this learning media are KSK students' competence in maharah kitabah, the habit of writing in Arabic and having competence in understanding the rules of nahwu and shorrof.